An investigation into the success rates of students with no prior accounting knowledge in obtaining a professional accounting degree - Rossouw, M.; Brink, S.M. (South African Journal of Higher Education, 2021)
Several South African universities do not require students to have completed Accounting at secondary school level in order to enrol for a degree in Accounting. At Stellenbosch University such students with no prior Accounting knowledge can still graduate and receive a Bachelor of Accounting degree (which is the first step of many towards becoming a CA (SA)) within the minimum time frame of three years given that an Accounting conversion examination is passed at the beginning of their second academic year. The literature on student performance where students have no prior Accounting knowledge focuses predominantly on first-year Accounting students. Limited studies have been expanded beyond the first academic year to investigate these students’ academic career up to their final year and whether such students obtain a professional degree in Accounting. The main objective of the research reported in this article was to analyse the results of first-year conversion students (with no prior Accounting knowledge) in order to report on their success rate towards obtaining a Bachelor of Accounting degree within the minimum time of three years. In order to meet this objective, a quantitative research method was applied. It was found that half of the population was successful in obtaining their professional degree in Accounting within three years and 81 per cent of the conversion students eventually obtained their professional degree in Accounting (irrespective of time). This finding suggests that Accounting as a subject at secondary school is not necessarily essential in order to obtain a professional degree in Accounting. Receiver operating curve analyses were also done to predict optimal cut-off marks for Accounting subjects in order to obtain the desired degree within three years. These predictions, together with the actual marks obtained by the identified population, should be welcomed by prospective conversion students who now have more data available for decision-making.